In vitro screening of natural feed additives from crustaceans, diatoms, seaweeds and plant extracts to manipulate rumen fermentation. (4th November 2015) - Belanche, Alejandro; Ramos‐Morales, Eva; Newbold, C Jamie
Abstract: BACKGROUND: Eight natural products from animal, unicellular algae, brown seaweed and plant origins were chosen according to their theoretical antimicrobial activity: Diatomaceous earths (DE), insoluble chitosan (ICHI), soluble chitosan (CHI), seaweed meal (SWM), Ascophyllum nodosum (ASC), Laminaria digitata (LAM), neem oil (NOIL) and an ivy fruit extract rich in saponins (IVY). Dose–response incubations were conducted to determine their effect on rumen fermentation pattern and gas production, while their anti‐protozoal activity was tested using 14 C‐labelled bacteria. RESULTS: DE, SWM, NOIL and ICHI had very small effects on rumen function when used at inclusion rate up to 2 g L −1 . ASC had anti‐protozoal effects (up to −23%) promoting a decrease in gas production and methanogenesis (−15%). LAM increased VFA production (+7%) and shifted from butyrate to acetate. CHI also shifted fermentation towards propionate production and lower methane (−23%) and protozoal activity (−56%). IVY decreased protozoal activity (−39%) and ammonia concentration (−56%), as well as increased feed fermentation (+11% VFA concentration) and shifted from acetate to propionate production. CONCLUSIONS: ASC, LAM, CHI and IVY showed promising potential in vitro as feed additives to improve rumen function, thus more research is needed to investigate their mode of action in the rumen microbial ecosystem. © 2015 Society of Chemical Industry